Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016 IEEE 2nd International Forum on Research and Technologies for Society and Industry Leveraging a Better Tomorrow (RTSI) 2016
DOI: 10.1109/rtsi.2016.7740573
|View full text |Cite
|
Sign up to set email alerts
|

Layered ensemble model for short-term traffic flow forecasting with outlier detection

Abstract: Real time traffic flow forecasting is a necessary requirement for traffic management in order to be able to evaluate the effects of different available strategies or policies. This paper focuses on short-term traffic flow forecasting by taking into consideration both spatial (road links) and temporal (lag or past traffic flow values) information. We propose a Layered Ensemble Model (LEM) which combines Artificial Neural Networks and Graded Possibilistic Clustering obtaining an accurate forecast of the traffic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Synthetic data sets containing concept drift (we select the Gaussian and electricity data sets) were generated using the Matlab program ConceptDriftData.m 4 [19]. We also Integrated our model in a traffic flow management system [20].…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic data sets containing concept drift (we select the Gaussian and electricity data sets) were generated using the Matlab program ConceptDriftData.m 4 [19]. We also Integrated our model in a traffic flow management system [20].…”
Section: Resultsmentioning
confidence: 99%
“…An online boosting approach for traffic flow forecasting under abnormal conditions was developed by Wu et al [21]. A layered ensemble model for short‐term traffic flow forecasting was proposed by Abdullatif et al [22]. Hamner [23] applied the random forest algorithm to predict travel‐time and showed that the proposed model outperformed other models in terms of estimation precision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 An urban area of the city of Genoa, a town in the north-west of Italy, was mapped with the aid of Open Street Map data available at https://www.openstreetmap.org. Traffic parameters were obtained from actual observations and several days of traffic were simulated by using the SUMO open source traffic simulator [32].…”
Section: Data Setsmentioning
confidence: 99%
“…We focus on the online approach to track and adapt to concept drift and shift and on using this knowledge to improve the ensemble forecasting model that was proposed in [1] by making the model able to not only detect outliers, but also track the changes in data streams.…”
Section: Introductionmentioning
confidence: 99%